Kepemimpinan Intrapreneurship, Budaya Sekolah dan Kinerja Inovasi Guru - Agus Wibowo; Ari Saptono (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2017)
This article aims to determine the relationship intrapreneurial leadership, school culture and innovation performance of elementary school teachers in East Jakarta. This research uses survey method with correlation approach. The results showed that there was a significant correlation between intrapreneurial leadership and school culture on teacher innovation performance of elementary school in East Jakarta where the result of double correlation coefficient test (Ry.12) = 0,885 and F count (F Change) = 266,395, and p -value = 0,000 <0.05, and While the coefficient of determination (R square) = 0,784, which means that the intrapreneurial leadership (X1) and school culture (X2) together influence 78,4% to the performance of innovation (Y). Keywords: Intrapreneurial Leadership, School Culture, Teacher's Innovation Performance